The engendered spaces in the village at the edge of the capital: A case study of Al Gharaza/ Sudan - Balghis Badri; Hardine Knuth (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2008)
This research is the outcome of fieldwork undertaken between November 2002 and 2003 in Al Gharaza village part of Khartoum State - the Sudan capital. The study focuses on identifying how spaces and times are interrelated and engendered. The forces that impact the creation of boundaries or those that direct change are analysed. How women's boundaries and spaces are defined and their interaction with them and bringing about new arrangements for spaces is discussed. How time is used, division of labour engendered, time conceptualized are highlighted. It is found that tradition and customs of exclusiveness as a value create a siege binding women spaces within the village and impact on their use of time: education is an important force that manages to crack the siege and open up to women some public space within the village. Outside forces for development or Islamization remained distant from the village; the villagers themselves desired a state of being apart from theses forces. The consequence is a situation of exclusiveness from both economic development efforts and political integration. The value of exclusiveness of 'others', inclusiveness from within; of the 'we' and 'they' have made the villagers to lead self-social development, which they desire and could afford, such as 'building schools and supporting teachers'. The interface between development, culture and social structures of the village life became evident. Minimal outside efforts to introduce development did not sustain. This made villagers step forward to initiate their own development, while development they doubt its consequenses is resisted. ... – – bis Ende 2003 in Al Gharaza, einem Dorf in Khartum State, durchgeführt wurde. Das Ziel der Untersuchung bestand darin zu untersuchen, wie Raum und Zeit miteinander verknüpft und wie sie geschlechtsspezifisch geprägt sind. Die begrenzenden Wirkungskräfte und die Faktoren, die sozialen Wandel einleiten, werden analysiert. Es wird diskutiert, wie die Räume der Frauen und ihre Grenzen definiert sind und wie neue Arrangements entstehen. Es wird herausgearbeitet, wie Zeit genutzt wird, welche Zeitkonzepte existieren und wie Arbeitsteilung geschlechtsspezifisch geprägt ist. Ergebnis der Untersuchung ist, dass Tradition und Exklusivität als zentraler Wert Frauen an das Dorf binden und die Verwendung ihrer Zeit bestimmen. Bildung ist ein wichtiger Faktor, Grenzen aufzubrechen und Frauen einen öffentlichen Raum im Dorf zu öffnen. Kräfte von außerhalb - wie Entwicklung und Islamisierung - bleiben fremd. Die Dorfbewohner selbst wollen sie vom Dorf fern halten. Daraus folgt ein Ausgeschlossensein von ökonomischer Entwicklung und politischer Integration. ...
Keywords: 330; Sudan; Women in rural areas; Space and time; Gender specific division of labour; Social change in rural areas Sudan; Frauen im ländlichen Raum; Raum und Zeit; Geschlechterspezifische Arbeitsteilung; Sozialer Wandel auf dem Lande